Die Entwaldungsvorgänge des 19. Jahrhunderts in der Basilicata (Süditalien) und ihre Folgen - Tichy, Franz (ERDKUNDE, 1957)
The author has set himself the task of investigating as exactly as possible the processes of deforestation in the Basilicata. Archive studies revealed information about great clearing activity during the 19th century. Beyond the already known uncertain overall data regarding the cleared areas it was possible by means of the applications for clearing (forest law of 1826) to find out the location and time of clearing of the respective areas. To locate the extensive areas cleared after the forest law of 1877 is rarely possible by means of archive studies. Particularly large and continuous cleared areas are situated in the hill country of the north eastern Basilicata where most of the land belongs to great landowners. The cause of the deforestation is considered to be the extremely rapid population increase during the 19th century which led to land scarcity and emigration since no agricultural reform (i. e. a land reform and intensification of cultivation) was carried out on a sufficiently large scale; a reform of this kind has only just started now. As consequences of the long lasting extensive use of the forest (i. e. pasture, charcoal burning, fires) and the active deforestation (i. e. clearing) must be considered the destructive landslips (franae) of various scale and manifold forms, particularly in the flysch mountains and Pliocene hills with clay soils. A special clause in the permissions for clearing gave in the hill country in places rise to park type landscapes where isolated oak trees (Quercus Cerris and Quercus Ilex) are found on the arable land. At present great efforts are being made to carry out reafforestation financed by the state, e. g. in the region of the upper Agri. It seems, however, that a final consolidation of the forests and of silviculture, whose success in the few existing state forests (Gallipoli-Cognato, Rifreddo, Monticchio) is noteworthy, will only be possible after a genuine agricultural reform has been accomplished. Such reform is, however, faced with obstacles some of which appear even today to be insurmountable, such as unfavourable conditions of climate and soil, the sites of the settlements and conditions of land ownership, as well as the general level of education and the lack of capital of the population.